Acute renal response to large doses of intravenous prednisolone in kidney homograft recipients and in normal subjects - POPOVTZER, MORDECAI M. (1971)
The immediate renal response to large intravenous doses of prednisolone was studied in 18 kidney homograft recipients and in 6 normal subjects. Clearance rates of inulin (C(IN)), creatinine (C(CR)), p-aminohippurate (C(PAH)), and electrolytes were measured over 3 one-hour periods following intravenous infusion of prednisolone (1 Gm.) and compared with corresponding clearance rates after a placebo infusion. C(IN), C(CR), and C(PAH) rates and [Formula: see text] ratios exhibited a substantial decrease during all collection periods following the infusion of prednisolone, both in the normal subjects and in the patients. Fractional excretion of potassium [Formula: see text] increased in a progressive fashion reaching peak values after 3 hours. Biphasic variations were observed in the fractional excretion of sodium [Formula: see text]; an increase during the first hour was followed by a decrease during the third hour. The changes in the fractional excretions of ultrafiltrable calcium [Formula: see text] , ultrafiltrable magnesium [Formula: see text] , and phosphorus [Formula: see text] were minimal. Normal subjects exhibited significant decreases in [Formula: see text] and [Formula: see text] following the infusion of prednisolone; there was no significant change in the patients. [Formula: see text] increased significantly both in the normal subjects and in the patients. These results indicate that acute suppression of kidney function is a general renal response to large doses of glucocorticoids. The marked decrease in the creatinine clearance ratio [Formula: see text] observed after the administration of prednisolone is consistent with a depressed tubular secretion of creatinine and emphasizes the inadequacy of C(CR) as an indication of glomerular filtration rate (GFR) under conditions in which large doses of glucocorticoids are employed.